Import Prices and the Exchange Rate - Tesař, Martin; Křečková Kroupová, Zuzana, 1972-; Taušer, Josef; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
The aim of this thesis is to examine the relation between import prices and the exchange rate and to estimate the exchange rate pass-through (ERPT) to import prices in different manufacturing industries in the Czech Republic. The first chapter familiarizes the reader with theoretical foundation of ERPT – the relation between import prices and the exchange rate, what it influences, its relation to inflation and presence of asymmetries within ERPT. The second chapter introduces the econometric model and data used in this thesis. The model tests not only the level of ERPT itself, but also asymmetries with respect to the direction and size of the change in the exchange rate. The monthly dataset covers the time period from January 2000 to May 2018. The third chapter shows the results of the empirical study – ERPT, long-run ERPT, asymmetries in ERPT with respect to direction and size of the change in the exchange rate and their combinations, and the development of ERPT over time.
Vedoucí práce: Zuzana Křečková Kroupová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses